An Investigation of Customer satisfaction Determinants: An Empirical Study in Jaffna District Private banking Sector - Sritharan, V.; Rajumesh, S. (Masilamani pathippagam, 2011)
The private banking sector in Jaffna grew rapidly speed after the post war conflict (2009). Along with its importance to the country’s economy, the level of competition has also increased. Many firms are focusing their efforts on maintaining a loyal customer base. This is particularly true in the financial services sector where deregulation has created an environment that allows consumers considerable choice in satisfying their financial needs. In response, many retail banks are directing their strategies towards increasing customer satisfaction and loyalty through improved service quality. By increasing loyalty a retail bank: reduces its servicing costs; gains knowledge of the financial affairs and needs of its customers; and has an opportunity to cross-sell existing and new products and services. Based on this background the present study is initiated to investigate the customer satisfaction determinants in private banking sector in Jaffna district of Sri Lanka. The sample is randomly made up of 87 customers, consisting of the customers from three private banks in Jaffna district of Sri Lanka. The data have been collected by using the structured questionnaire, which consist of two parts. Part 1 contain the questions related to the socio-demographic profiles of respondent. Part 2 contains 22 statements related to service quality, service features, customer complaint handling and customer satisfaction. The result relevant that, Services quality and Services features influence to determine Customer satisfaction of the private banks in Jaffna district. And service quality has a greater impact on customer satisfaction. The study could be quite useful from the policy perspective in providing the guidelines to develop proper strategies.
Keywords: Services quality; Services features; Customer complaint; Customer satisfaction; Private Banks